Neutrophils mediate edema formation but not mechanical allodynia during zymosan‐induced inflammation. Issue 1 (20th February 2014) - Suo, Jing; Linke, Bona; Meyer dos Santos, Sascha; Pierre, Sandra; Stegner, David; Zhang, Dong Dong; Denis, Cecile V.; Geisslinger, Gerd; Nieswandt, Bernhard; Scholich, Klaus
Abstract : Depletion of neutrophils, or blockage of neutrophil receptors, reduces zymosan‐induced neutrophil extravasation and edema formation, but not zymosan‐induced mechanical allodynia. Abstract : Inflammatory pain is based on stimulation and sensitization of peripheral endings of sensory neurons (nociceptors) by pronociceptive mediators. These mediators can be released by resident cells, as well as invading immune cells. Although neutrophils are known to release various mediators, which can stimulate or sensitize nociceptors, the extent of their contribution to nociceptive responses is unclear. Here, we studied the contribution of neutrophils to zymosan‐induced inflammatory pain, which is characterized by an early recruitment of high numbers of neutrophils. Surprisingly, antibody‐mediated neutrophil depletion caused a complete loss of edema formation but had no effect on mechanical pain thresholds. Blockage of the interaction between neutrophils and platelets or endothelial cells using antibodies directed against CD11b and CD162 reduced neutrophil recruitment to the site of inflammation. Again, the treatment decreased zymosan‐induced edemas without altering mechanical pain thresholds. Also, HLB‐219 mice, which have five to 10 times less platelets than WT mice, showed reduced neutrophil recruitment to the site of inflammation and decreased edema sizes, whereas, again, mechanical thresholds were unaltered. The effects observed in HLB‐219 mice were relatively small and not reproduced in vWF‐deficient mice or after antibody‐mediated blockage of GPIbα. Flow chamber and transmigration assays showed that platelets were not necessary for neutrophil adhesion to endothelial cells but increased their transmigration. Taken together, zymosan‐induced mechanical allodynia is, in contrast to edema formation, independent of neutrophils, and recruitment of neutrophils is only partly influenced by interactions with platelets.